Deletion of the N-Terminal Domain of Yeast Eukaryotic Initiation Factor 4B Reprograms Translation and Reduces Growth in Urea - Liu, Xiaozhuo; Moshiri, Houtan; He, Qian; Sahoo, Ansuman; Walker, Sarah E. (Frontiers in Molecular Biosciences, 2022)
The yeast eukaryotic initiation factor 4B binds the 40S subunit in translation preinitiation complexes (PICs), promoting mRNA recruitment. Recent evidence indicates yeast mRNAs have variable dependence on eIF4B under optimal growth conditions. Given the ability of eIF4B to promote translation as a function of nutrient conditions in mammalian cells, we wondered if eIF4B activities in translation could alter phenotypes in yeast through differential mRNA selection for translation. Here we compared the effects of disrupting yeast eIF4B RNA- and 40S-binding motifs under ~1400 growth conditions. The RNA-Recognition Motif (RRM) was dispensable for stress responses, but the 40S-binding N-terminal Domain (NTD) promoted growth in response to stressors requiring robust cellular integrity. In particular, the NTD conferred a strong growth advantage in the presence of urea, which may be important for pathogenesis of related fungal species. Ribosome profiling indicated that similar to complete eIF4B deletion, deletion of the NTD dramatically reduced translation, particularly ofthose mRNAs with long and highly structured 5-prime untranslated regions. This behavior was observed both with and without urea exposure, but the specific mRNA pool translated in response to urea differed. Deletion of the NTD also led to relative increases in translation of shorter transcripts with higher dependence on eIF4G, as was noted for eIF4B deletion. Gene ontology analysis indicated that proteins encoded by eIF4B NTD-dependent transcripts were associated with the cellular membrane system and the cell wall, while NTD-independent transcripts encoded proteins associated with cytoplasmic proteins and protein synthesis. This analysis highlighted the difference in structure content of mRNAs encoding membrane versus cytoplasmic housekeeping proteins and the variable reliance of specific gene ontology classes on various initiation factors promoting otherwise similar functions. Together our analyses suggest that the eIF4B NTD promotes cellular stress responses by modulating the capacity to translate a diverse mRNA pool.